Endoscopic stricturoplasty with linear stapler: an efficient alternative for the refractory rectal anastomotic stricture - Kouladouros, Konstantinos; Reißfelder, Christoph; Kähler, Georg (Digestive diseases and sciences, 2023)
Introduction: Symptomatic anastomotic stricture is a rare but major complication after left-sided colorectal surgery. Hydraulic balloon dilatation is the first-line treatment in cases where the complication occurs, but 20% of patients present with refractory strictures after multiple sessions. Endoscopic stricturoplasty with the use of a linear stapler is a novel therapeutic alternative for those difficult cases. Materials and Methods: We identified all patients in our department who underwent endoscopic stricturoplasty with a linear stapler between 2004 and 2022. The technical, periinterventional, and follow-up data of the patients were retrospectively analyzed. Results: We identified nine patients who fulfilled our inclusion criteria. The procedure was technically possible in eight cases, whereas in one case, the anatomy of the anastomosis did not allow for a correct placement of the stapler. All patients with a technically successful procedure were relieved from their symptoms and could have their ostomy reversed. There was no periprocedural morbidity and mortality. Two patients presented with a recurrent stricture eight and 26 months after the initial stricturoplasty, and the procedure was successfully repeated in both cases. Conclusions: Endoscopic stricturoplasty is a feasible, safe, and minimally invasive alternative for the treatment of refractory anastomotic strictures in the distal colon and rectum for patients with a suitable anatomy.
Online veröffentlicht: 19. Oktober 2023
Gesehen am 18.12.2023